NORMS, STANDARDS, PROCEDURES, AND LICENSING CRITERIA FOR CONSTRUCTION SERVICE BUSINESSES WITH FOREIGN INVESTMENT IN INDONESIA - Donald Franks Ginting; Dwi Putra Nugraha (Journal of Economic, Bussines and Accounting (COSTING), 2025)
Indonesia's construction industry has faced significant challenges in the past, mainly due to bureaucratic obstacles and regulatory uncertainties that deterred foreign investment. However, the sector has shown growth driven by the increasing demand for infrastructure development, which is essential for economic advancement. Key players in this industry include construction service companies (BUJK), some of which are linked to foreign investment (PMA). To manage the licensing process for PMA-affiliated BUJKs, the Indonesian government introduced Norms, Standards, Procedures, and Criteria (NSPK) to create a favorable investment climate while safeguarding national interests. This study evaluates the regulations and procedures foreign investors must comply with to establish and license construction companies in Indonesia. It also examines the impact of Law Number 6 of 2023, which governs the Job Creation Law, on investment in the construction sector. Using a normative-empirical approach, the research analyzes primary legal sources and gathers data through interviews with officials from the Ministry of Public Works and Investment, as well as construction law consultants. The findings reveal that the current regulations are generally effective in managing foreign investment, though challenges remain in verifying the completeness of data and documents for SBU applications. Delays often occur due to the lack of specific timeframes outlined in Ministerial Regulation PUPR Number 8 of 2022. The study concludes that regulatory reforms, particularly the introduction of clearer timelines for document verification, are necessary to avoid unnecessary delays.